Research on stochastic game and optimization in complex microgrid control - Hong ZHOU; Ruotian YAO; Chang YU; Zhongcheng LEI (智能科学与技术学报)
A microgrid which integrated by a large scale of distributed generators,storage equipment and dynamic loads has stochastic characteristics in both the power generation and the demand-side.The purpose was to discuss various decision-making and optimal control approaches in the integrated energy microgrid based on a stochastic game.Firstly,the characteristic and architecture of the future complex microgrid were investigated.Secondly,the form and interact of the group game were explained in details,respectively.Then,the stochastic characteristics of different players and the topology that affecting the game on complex microgrids were presented.Finally,a stochastic game optimization approach and its control architecture was proposed.By discussing the key issues of microgrid synchronization,stability and game optimization in different perspectives,the new ideas for promoting clean energy consumption,supply-demand side interaction and maintaining the stability of power grids were provided.